Kualitas Pelayanan Kesehatan Melalui Program E-Health - Lutfia Nurul Hidayati; Ghazie Etty Violindri (FISIP UWP, 2020)
The e-health program aims to support public health activities in general and improve the quality of health services. E-health is divided into two, namely e-health online through the web (can be done anywhere via the respective server network) and e-health manually (done at the Puskesmas which is directly assisted by the officer). There are still obstacles in e-health services, namely, people cannot operate online e-health and the availability of a lack of e-health machines. This research method is a qualitative descriptive, research location in the Kalirungkut Public Health Center, Rungkut District, Surabaya City. The data used are primary and secondary data, obtained from the informants selected based on purposive sampling. The results of this study indicate that in the tangibles (physical evidence) criteria, the Kalirungkut Health Center in Surabaya City has good service conditions but in some cases it needs attention, for example the number of machines that are felt to be added. Reliability, has done it well. Response (response / response) various efforts have been made to overcome problems related to Puskesmas services. Assurance, the knowledge and politeness of employees is good enough. Empathy (Empathy), It has been done very well by the Kalirungkut Health Center in Surabaya City. This is because the Puskesmas performs services by applying the principle of equal rights to receive services.